2008
DOI: 10.1175/2007jcli2094.1
|View full text |Cite
|
Sign up to set email alerts
|

Absorbing Aerosols and Summer Monsoon Evolution over South Asia: An Observational Portrayal

Abstract: The South Asian haze builds up from December to May, is mostly of anthropogenic origin, and absorbs part of the solar radiation. The influence of interannual variations of absorbing aerosols over the IndoGangetic Plain in May on the Indian summer monsoon is characterized by means of an observational analysis. Insight into how the aerosol impact is generated is also provided.It is shown that anomalous aerosol loading in late spring leads to remarkable and large-scale variations in the monsoon evolution. Excessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
150
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 50 publications
5
150
0
Order By: Relevance
“…However, a recent study of Li and Leung (2013) showed that the interdecadal summer precipitation variability in China is related to the Arctic spring warming. It has been also recently reported that the rainfall over the Indian monsoon rainfall, particularly over the northeast part, and northern China has a declining trend (Bollasina and Nigam 2008;Bollasina et al 2011) but that over the Yangzte-Huai River valley and South Korea has an increasing trend Choi et al 2010;Preethi et al 2016).…”
Section: Interannual To Interdecadal Linkages: a Reviewmentioning
confidence: 92%
“…However, a recent study of Li and Leung (2013) showed that the interdecadal summer precipitation variability in China is related to the Arctic spring warming. It has been also recently reported that the rainfall over the Indian monsoon rainfall, particularly over the northeast part, and northern China has a declining trend (Bollasina and Nigam 2008;Bollasina et al 2011) but that over the Yangzte-Huai River valley and South Korea has an increasing trend Choi et al 2010;Preethi et al 2016).…”
Section: Interannual To Interdecadal Linkages: a Reviewmentioning
confidence: 92%
“…These reasons provide a comprehensive motivation to quantify the 8272 A.-P. Hyvärinen et al: Part 1: PM and BC concentrations effect of the monsoon on aerosols in the area. In addition, it's well known that aerosols can modulate the monsoon and thus the whole water cycle (Lau and Kim, 2006;Bollasina et al, 2008;Meehl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, during a break, aerosol concentration builds up in central and north India through local emissions and long range transports while the north Indian Ocean remains relatively pristine. As a large fraction of these aerosols is of absorbing type (Menon 2004;Chakraborty et al 2004;Bollasina et al 2008), they would cool the surface but warm the atmospheric layer between 1 and 3 km. Such warming of the lower atmosphere over central and north India and lack of it over the north Indian Ocean would lead to a north-south temperature gradient at this level and convergence of moisture to central and north India.…”
Section: Introductionmentioning
confidence: 99%